El juego teatral y la prelectura en los niños de Primer año de Educación Básica de la Unidad Educativa Fiscomisional “San José de Calasanz” del Cantón Saraguro, Provincia de Loja. - Medina Ordoñez, Michelle Valeria (2024)
The present investigation applied in the "San José de Calasanz" Fiscomisional Educational Unit of the Saraguro Canton, Province of Loja. The research objective was to establish the theatrical game as a pedagogical tool for teaching and participation in pre-reading. Theatrical play in children can promote and stimulate language, body expression, and gestures supported by sensitive components to achieve the scenes. To this extent, it is a tool that makes it easier to achieve the objectives set and is shown as a playful and integrative resource that considers the learning process and not just the result. Methodologically, the research has a non-experimental qualitative and quantitative approach; since there was no manipulation of variables with an exploratory depth of study, it allowed us to be creative and obtain more precise information about the topic to be investigated, in the descriptive we seek to describe in detail the essential properties that allow measuring and evaluating various aspects to be explored, in the field because it was carried out at the scene of the events. A bibliographic investigation using data from books, magazines, digital repositories, and articles allowed for information collection and achieving the proposed objectives. The observation technique was applied, and as an instrument, the observation sheet directed for children, which consists of 10 indicators related to the topic investigated, was used. The two variables resulted in little use of theatrical play and pre-reading in the classroom.